Cutout shape and reinforcement design for composite C-section beams under shear load - Guo, Shijun J.; Morishima, R.; Zhang, Xiang; Mills, Andrew (Elsevier, 2009)
This paper reports a study of the performance of two forms of cutout and various edge reinforcements in a composite C-section beam under static shear load. Firstly, cutout shape effect on stress concentration was studied. This was followed by a comparative study of a range of reinforcement doublers, which were 20 mm wide rings made of a steel alloy or composite laminate, or by a novel fibre tow placement technique. The comparisons are made in terms of the stress and strain reductions at a hot spot at the cutout edge. Good agreement between the numerical and test results has been achieved for different cutout shapes and reinforcements, and this study has demonstrated that the cutout induced stress concentration can be reduced significantly by appropriate cutout shape and edge reinforcements. The stress reduction magnitude is found to be strongly related to the stiffness of the reinforcement rings. The diamond-shaped cutout and the fibre tows reinforcement show clear advantages over the widely adapted circular cutout and laminated ring reinforcement. These findings should contribute to future design improvement of composite aircraft structures in similar shape and loading conditions.
Keywords: Cutout; edge reinforcement; composite channel section; C-section beam; fibre tow placement